STUDIES ON BEGONIA(BEGONIACEAE) OF THE MOLUCCA ISLANDS I: TWO NEW SPECIES FROM HALMAHERA, INDONESIA AND AN UPDATED DESCRIPTION OF BEGONIA HOLOSERICEA - Wisnu H Ardi; Yayan W . C. Kusuma; Carl L. Lewis; Rosniati A. Risna; Harry Wiriadinata; Melissa E. Abdo; Daniel C. Thomas (Research Center for Biology, 2014)
Two new species of Begonia, Begonia holosericeoides Ardi & D. C. Thomas and B. aketajawensis Ardi & D. C. Thomas, are described from Aketajawe Lolobata National Park, Halmahera, Indonesia. The two species belong to Begonia section Petermannia. Begonia holosericea, previously only tentatively assigned to a section, is here assigned to section Petermannia based on the examination of newly available material. Additionally, a revised description and an illustration are provided. A key to the Moluccan species of Begonia is presented.